PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA STRATEGIS DALAM MENINGKATKAN KINERJA INSTANSI PEMERINTAH: STUDI LITERATUR - Utama, Zahera Mega; Melinda; Syahbana, Azwin Firman; Yosie, Yosie (Jurnal Pijar, 2025)
The implementation of Strategic Human Resource Management (SHRM) in Indonesia’s public sector reflects a shift from administrative HR practices toward a strategic approach aligned with bureaucratic reform and the improvement of public service delivery. This study aims to analyze how SHRM is applied within government institutions and its impact on organizational performance. Employing a literature review method, this study draws upon national policies, official government reports, and previous research findings. The results indicate that the integration of HR functions with organizational strategy, the implementation of a merit system, digital transformation in HR processes, and the strengthening of transformational leadership significantly contribute to improving bureaucratic effectiveness. However, key challenges remain, including limited managerial capacity, organizational resistance to change, and disparities in implementation across institutions. The study highlights the importance of policy consistency, digital ecosystem development, and enhancing the strategic literacy of civil servants in ensuring successful SHRM implementation. These findings offer valuable insights for policymakers and practitioners in designing more adaptive and sustainable HR strategies in the Indonesian public sector.